Anti-Corruption Education Values in Local Javanese Cultural Wisdom - Putri, Noviani Achmad; Handoyo, Eko; Martitah, Martitah; Mustofa, Moh. Solehatul (Universitas Negeri Semarang, 2024)
Anti-Corruption education will continue to be needed with the aim of producing an honest generation for Indonesia. Local Javanese cultural wisdom has an important role in instilling Anti-Corruption Education values such as the values of honesty, discipline, simplicity, fairness, caring, hard work, independence, introspection and courage. The purpose of this study is to analyze the implementation strategy of instilling anti-corruption education values based on local wisdom of Javanese culture. This research method is descriptive qualitative research. The research setting in this study was State Middle Schools 4, 8, 19 Semarang Cyty, SMP Nasima dan SMP Al-Azar Semarang City. The data sources for this research are primary data sources, namely social studies teachers, students and school principals. Secondary data such as teaching modules, attitude journals, documentation, books, magazines, newspapers, written archives that are directly related to the object. Data collection techniques through observation, interviews and documentation. Test the validity of the data using source triangulation and engineering triangulation techniques. The data analysis technique uses interactive analysis of data collection, data reduction, data presentation and verification. The results of this research are local Javanese cultural wisdom values that are relevant to Anti-Corruption Education such as